Think better : an innovator's guide to productive thinking (your company's future depends on it, and so does yours) - Hurson, Tim (McGraw-Hill, 2008)
Providing numerous examples and illustrations; this straightforward guide introduces Productive Thinking; a practical; easy-to-learn; repeatable process that helps people understand more clearly; think more creatively; and plan more effectively. --